Birla Carbon expands cleaner products production in India. Issue 8 (August 2021) - Unknown
Abstract : Birla Carbon has announced the large-scale availability of clean carbon black products in India by expanding the production capacity at its Gummidipoondi plant. The newly introduced production line will make available globally approved cleaner products in India.